Composite negative electrode and preparation method thereof, solid-state lithium battery

CN117476875BActive Publication Date: 2026-10-27CHINA FAW CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311152951.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2026-10-27
Estimated Expiration
2043-09-07

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种复合负极及其制备方法、固态锂电池,以解决现有技术中由于固态锂电池中合金层扩散动力学慢导致的电压平台下降的问题

Benefits of technology

[0020]应用本发明的技术方案,相对于现有技术,本发明的复合负极是在液态合金层与活性锂金属层之间插入了一层扩散层,对扩散层进行预锂化有利于提高扩散层的电负性和亲锂性,同时使得锂原子能够更快速的从扩散层中脱出,凭借该扩散层的过渡作用,实现脱锂机制的转变从而提高合金层中锂原子扩散系数,可以提高液态合金层中锂扩散动力学,提高界面锂扩散能力,解决电池电压平台下降的问题。并且通过在扩散层表面构筑保护层提高复合负极与固态电解质材料界面之间的固-固相容性问题,降低界面阻抗和抑制锂枝晶生长从而有利于提高固态电池的电化学性能。同时,本发明所提供的复合负极中含有液态合金层,即在常温下呈现液态,且相对于固态而言,液态有着更小的空间位阻,因而该复合负极用作锂电池负极时,负极生长的锂枝晶会优先选择在液态合金中生长,而不会选择朝向固态电解质(聚合物电解质层)中生长,从而可有效降低因锂枝晶生长导致电池内短路的概率,从而大大提高了电池的安全性能;不仅如此,该液态合金层还有着极好的锂离子传输性能,且本发明所提供的负极中的液体合金层靠近固态电解质放置,相较于负极中的固态物质与固态电解质接触而言,液态合金层与固态电解质层的接触性更好,更有利于锂离子的传输;此外,液态合金层还具有优异的电子导电性,同时有助于电子的传输,使得负极能够快速的进行电化学反应,降低负极阻抗,从而有助于提高和改善电池的整体性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117476875B_ABST
    Figure CN117476875B_ABST
Patent Text Reader

Abstract

The application provides a composite negative electrode and a preparation method thereof, and a solid-state lithium battery. The composite negative electrode comprises a protection layer, a diffusion layer, an active layer and a negative electrode current collector which are sequentially stacked, wherein the diffusion layer comprises pre-lithiated lithium-intercalation materials and / or pre-lithiated materials capable of reversibly forming alloys or compounds with lithium, and the protection layer comprises a liquid alloy layer and a polymer electrolyte layer which are sequentially stacked, and the liquid alloy layer is in contact with the diffusion layer. The composite negative electrode can improve the lithium diffusion kinetics in the liquid alloy layer, improve the lithium diffusion capacity of the interface, and solve the problem of voltage platform drop of the battery. At the same time, the probability of internal short circuit of the battery caused by lithium dendrite growth can be effectively reduced, and the safety performance of the battery is greatly improved. In addition, the liquid alloy layer also has excellent electronic conductivity, which is helpful for the transmission of electrons, so that the negative electrode can quickly perform electrochemical reaction, reduce the negative electrode impedance, and help to improve and improve the overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state lithium battery technology, and more specifically, to a composite negative electrode and its preparation method, and a solid-state lithium battery. Background Technology

[0002] Currently, with the rapid development of the electric vehicle industry, the demand for battery energy density, safety, reliability, and cycle life is soaring. Lithium metal has an extremely high theoretical specific capacity (3860 mAh·kg⁻¹). -1 With its extremely high energy density and lowest potential (-3.04V), lithium metal secondary batteries are considered the most promising energy storage devices and have attracted much attention. However, the traditional electrolyte-separator system uses low-boiling-point toxic organic solvents, posing a risk of electrolyte leakage, combustion, and explosion, resulting in serious safety hazards. Therefore, developing next-generation high-energy-density, high-safety solid-state lithium batteries is a cutting-edge issue and key technology for efficient and safe energy storage, and an indispensable support for meeting the country's strategic needs in the new energy field.

[0003] However, the interface problem between the solid electrolyte and the lithium metal anode limits the performance of solid-state batteries. The interface between the solid electrolyte and the electrode mainly faces the following challenges: 1) Poor physical contact: The contact between the electrode and the electrolyte is a solid-solid point contact. The small contact area results in high interfacial contact impedance, and the volume effect of the electrode material during cycling further causes contact failure, leading to uneven lithium-ion deposition and slow transfer kinetics, which directly limits battery performance. 2) Numerous voids exist in the solid electrolyte layer, which are easily pierced by lithium dendrites during cycling, causing micro-short circuits and reducing the battery's cycle life. 3) Due to the significant volume expansion and contraction of lithium metal during charging and discharging, mechanical damage is caused to the solid electrolyte layer in direct contact with it. Ultimately, the electrolyte layer cracks due to mechanical stress, resulting in irreversible damage to the battery.

[0004] Chinese patent application CN112420978A discloses a composite negative electrode, a solid-state lithium battery, and a method for preparing the same. The provided negative electrode consists of a lithium metal foil and a liquid alloy layer stacked together. When used as a lithium battery negative electrode, lithium dendrites preferentially grow in the liquid alloy rather than towards the solid electrolyte, effectively reducing the probability of internal short circuits caused by lithium dendrite growth and significantly improving battery safety. Furthermore, the liquid alloy in the provided negative electrode is placed close to the solid electrolyte, resulting in better contact between the liquid alloy and the solid electrolyte layer compared to contact between the solid material and the solid electrolyte in the negative electrode itself, which is more conducive to lithium-ion transport. In addition, the liquid alloy has excellent electronic conductivity, further facilitating electron transport and enabling the negative electrode to undergo rapid electrochemical reactions, reducing negative electrode impedance and thus contributing to improved overall battery performance. Although the method provided by this invention can form a uniform alloy protective layer on the surface of the negative electrode, since the alloy layer in solid-state lithium batteries is conducted through atomic diffusion, as the phase composition of the alloy layer becomes more complex during the battery discharge process, the interfacial lithium diffusion capacity decreases significantly, causing the battery voltage plateau to drop, which further leads to uneven lithium extraction and ultimately battery failure. Summary of the Invention

[0005] The main objective of this invention is to provide a composite negative electrode and its preparation method, as well as a solid-state lithium battery, to solve the problem of voltage plateau drop caused by slow diffusion kinetics of alloy layers in solid-state lithium batteries in the prior art.

[0006] To achieve the above objectives, according to one aspect of the present invention, a composite negative electrode is provided, comprising a protective layer, a diffusion layer, an active layer, and a negative electrode current collector stacked sequentially, wherein the diffusion layer comprises a pre-lithiated lithium-intercalable material and / or a pre-lithiated material capable of reversibly forming an alloy or compound with lithium, and the protective layer comprises a liquid alloy layer and a polymer electrolyte layer stacked sequentially, wherein the liquid alloy layer is disposed in contact with the diffusion layer.

[0007] Furthermore, the aforementioned lithium-intercalable materials are selected from any one or more of porous carbon materials, graphite, lithium titanate, transition metals, bismuth fluoride oxides, and bismuth fluoride oxides; the materials that can reversibly form alloys with lithium are selected from any one or more of elemental silicon, elemental silver, elemental germanium, elemental gold, elemental platinum, and elemental tin; and the materials that can reversibly form compounds with lithium are selected from any one or more of transition metal oxides and silicon oxides.

[0008] Furthermore, the pore size of the porous carbon material is 1 nm to 40 μm, preferably 0.1 to 5 μm; the porosity of the porous carbon material is 20% to 85%, preferably 40% to 60%.

[0009] Furthermore, the active layer is composed of elemental lithium metal, and the mass of elemental lithium metal is 5 to 90 wt% of the total mass of the active layer, diffusion layer, and protective layer.

[0010] Furthermore, the thickness of the diffusion layer is 1 μm to 80 μm, and the loading of the diffusion layer is 0.1 to 10 mg / cm³. 2 .

[0011] Furthermore, the melting point of the liquid alloy layer is -40 to 35°C, and the alloying elements in the liquid alloy layer are selected from any two or more elements selected from the following elements: Na, K, Ga, Sn, In, Hg, Al, Mg, Zn, Bi, Pd, Cd, and Tl; and / or, the thickness of the liquid alloy layer is 10 nm to 30 μm, and the loading of the liquid alloy layer is less than 20 mg / cm³. 2 .

[0012] Furthermore, the material form of the aforementioned negative electrode current collector is one-dimensional, two-dimensional, three-dimensional, or a combination thereof.

[0013] Furthermore, the structure of the aforementioned negative electrode current collector is selected from any one or more of the following: granular structure, fiber structure, layered structure, or three-dimensional network structure or three-dimensional foam cavity structure formed by interwoven layers.

[0014] Furthermore, the average particle size of the above-mentioned particle structure is 0.5 mm to 50 mm, the thickness of the layered structure is 1 μm to 100 μm, the cavity size in the three-dimensional foam cavity structure is 5 nm to 100 μm, and the thickness of the three-dimensional skeleton in the three-dimensional network structure and the three-dimensional foam cavity structure is 2 μm to 1 mm.

[0015] Furthermore, the aforementioned negative electrode current collector is selected from copper balls, copper wires, zinc wires, aluminum wires, nickel wires, iron wires, titanium wires, iron-nickel alloy wires, copper foil, zinc foil, aluminum foil, nickel foil, iron foil, titanium foil, iron-nickel alloy foil, carbon film, carbon cloth, carbon paper, carbon fiber, graphene, MXene, conductive polymer non-metallic materials, foamed copper, foamed zinc, foamed nickel, foamed aluminum, foamed iron, foamed titanium, or foamed iron-nickel alloy, wherein the conductive polymer non-metallic material is selected from any one or more of polypyrrole compounds, polyphenylene sulfide compounds, polyaniline compounds, polythiophene compounds, poly(p-phenylene) compounds, and polyphthalocyanine compounds.

[0016] According to another aspect of the present invention, a method for preparing the above-mentioned composite negative electrode is provided, the method comprising: step S1, loading an active layer onto a negative electrode current collector to obtain a bilayer structure material; step S2, loading a lithium-intercalating material and / or a material that can reversibly form an alloy or compound with lithium onto the active layer of the bilayer structure material to obtain a supported structure material; step S3, heating the supported structure material to pre-lithiate the lithium-intercalating material and / or the material that can reversibly form an alloy or compound with lithium into a diffusion layer, thereby obtaining a diffusion layer-active layer-current collector three-layer structure material; and step S4, contacting and laminating the diffusion layer with a liquid alloy layer of a protective layer to obtain a composite negative electrode; wherein the protective layer comprises a liquid alloy layer and a polymer electrolyte layer stacked sequentially.

[0017] Furthermore, the heating temperature is 80–170°C, and the heating time is 2–10 hours.

[0018] Furthermore, the above preparation method also includes a protective layer preparation process, which includes: loading a slurry comprising a polymer, a lithium salt, and a solvent onto a substrate, drying it to obtain a polymer electrolyte layer; loading a liquid alloy onto the polymer electrolyte layer to obtain a protective layer; the mass ratio of polymer to lithium salt is 1:20 to 50:1, preferably 1:1 to 20:1; the polymer is a self-polymer or copolymer, and the monomers forming the polymer are selected from any one or more of amides, urethanes, ethers, carbonates, vinylidene fluoride, acrylonitrile, vinyl chloride, and ethylene oxide; and / or, the lithium salt is selected from any one or more of LiPF6, LiBF4, LiAsF6, LiDFOB, LiPO2F2, LiNO3, LiTFSI, or LFSI.

[0019] According to another aspect of the present invention, a solid-state lithium battery is provided, comprising a negative electrode, the negative electrode being the aforementioned composite negative electrode.

[0020] Compared to existing technologies, the composite anode of this invention incorporates a diffusion layer inserted between the liquid alloy layer and the active lithium metal layer. Pre-lithiation of the diffusion layer enhances its electronegativity and lithiophilicity, allowing lithium atoms to escape more rapidly. This diffusion layer facilitates a transition in the delithiation mechanism, thereby increasing the lithium atom diffusion coefficient in the alloy layer. This improves lithium diffusion kinetics in the liquid alloy layer, enhances interfacial lithium diffusion capacity, and addresses the issue of battery voltage plateau decline. Furthermore, constructing a protective layer on the diffusion layer surface improves solid-solid compatibility between the composite anode and the solid electrolyte material, reduces interfacial impedance, and inhibits lithium dendrite growth, thus enhancing the electrochemical performance of the solid-state battery. Meanwhile, the composite negative electrode provided by this invention contains a liquid alloy layer, which is liquid at room temperature. Compared with the solid state, the liquid state has less steric hindrance. Therefore, when this composite negative electrode is used as a lithium battery negative electrode, the lithium dendrites growing on the negative electrode will preferentially grow in the liquid alloy rather than towards the solid electrolyte (polymer electrolyte layer). This can effectively reduce the probability of internal short circuits caused by lithium dendrite growth, thereby greatly improving the battery's safety performance. Moreover, the liquid alloy layer also has excellent lithium-ion transport performance. Furthermore, the liquid alloy layer in the negative electrode provided by this invention is placed close to the solid electrolyte. Compared with the contact between the solid material and the solid electrolyte in the negative electrode, the contact between the liquid alloy layer and the solid electrolyte layer is better, which is more conducive to lithium-ion transport. In addition, the liquid alloy layer also has excellent electronic conductivity, which also helps electron transport, enabling the negative electrode to carry out electrochemical reactions quickly, reducing the negative electrode impedance, and thus helping to improve the overall performance of the battery. Attached Figure Description

[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0022] Figure 1 A schematic diagram of a composite negative electrode provided in Embodiment 1 of the present invention is shown;

[0023] Figure 2 The charge-discharge curves of solid-state lithium batteries provided in Embodiment 1, Comparative Example 1, and Comparative Example 2 of the present invention are shown.

[0024] The above figures include the following reference numerals:

[0025] 1. Protective layer; 2. Diffusion layer; 3. Active layer; 4. Negative electrode current collector. Detailed Implementation

[0026] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0027] As analyzed in the background section, the existing technology suffers from a voltage plateau drop due to the slow diffusion kinetics of the alloy layer in solid-state lithium batteries. To address this issue, this application provides a composite negative electrode, its preparation method, and a solid-state lithium battery.

[0028] In a typical embodiment of this application, a composite negative electrode is provided, such as Figure 1 As shown, the composite negative electrode includes a protective layer 1, a diffusion layer 2, an active layer 3, and a negative electrode current collector 4 stacked sequentially. The diffusion layer 2 includes a pre-lithiated lithium-intercalable material and / or a pre-lithiated material that can reversibly form an alloy or compound with lithium. The protective layer 1 includes a liquid alloy layer and a polymer electrolyte layer stacked sequentially, with the liquid alloy layer in contact with the diffusion layer.

[0029] Compared to existing technologies, the composite anode of this invention incorporates a diffusion layer 2 inserted between the liquid alloy layer and the active lithium metal layer. Pre-lithiation of the diffusion layer 2 enhances its electronegativity and lithiophilicity, while simultaneously allowing lithium atoms to escape more rapidly. Through the transitional effect of the diffusion layer 2, a shift in the delithiation mechanism is achieved, thereby increasing the lithium atom diffusion coefficient in the alloy layer. This improves lithium diffusion kinetics in the liquid alloy layer, enhances interfacial lithium diffusion capacity, and addresses the issue of battery voltage plateau decline. Furthermore, constructing a protective layer on the surface of the diffusion layer 2 improves the solid-solid compatibility between the composite anode and the solid electrolyte material interface, reduces interfacial impedance, and inhibits lithium dendrite growth, thus contributing to improved electrochemical performance of the solid-state battery. Meanwhile, the composite negative electrode provided by this invention contains a liquid alloy layer, which is liquid at room temperature. Compared with the solid state, the liquid state has less steric hindrance. Therefore, when this composite negative electrode is used as a lithium battery negative electrode, the lithium dendrites growing on the negative electrode will preferentially grow in the liquid alloy rather than towards the solid electrolyte (polymer electrolyte layer). This can effectively reduce the probability of internal short circuits caused by lithium dendrite growth, thereby greatly improving the battery's safety performance. Moreover, the liquid alloy layer also has excellent lithium-ion transport performance. Furthermore, the liquid alloy layer in the negative electrode provided by this invention is placed close to the solid electrolyte. Compared with the contact between the solid material and the solid electrolyte in the negative electrode, the contact between the liquid alloy layer and the solid electrolyte layer is better, which is more conducive to lithium-ion transport. In addition, the liquid alloy layer also has excellent electronic conductivity, which also helps electron transport, enabling the negative electrode to carry out electrochemical reactions quickly, reducing the negative electrode impedance, and thus helping to improve the overall performance of the battery.

[0030] Furthermore, the preferred lithium-intercalating material is selected from any one or more of porous carbon materials, graphite, lithium titanate, transition metals, bismuth fluoride oxides, and bismuth fluoride oxides; the material that can reversibly form an alloy with lithium is selected from any one or more of elemental silicon, elemental silver, elemental germanium, elemental gold, elemental platinum, and elemental tin; and the material that can reversibly form a compound with lithium is selected from any one or more of transition metal oxides and silicon oxides.

[0031] In some embodiments of this application, the pore size of the porous carbon material is preferably 1 nm to 40 μm, preferably 0.1 to 5 μm, and the porosity of the porous carbon material is 20 to 85%, preferably 40 to 60%. This helps to alleviate the volume expansion effect of the active layer and provides more lithium insertion sites for lithium-containing materials, thereby inserting more lithium ions and improving the lithium diffusion capacity in the liquid alloy layer.

[0032] In some embodiments of this application, the active layer is elemental lithium metal, and the mass of elemental lithium metal is 5 to 90 wt% of the total mass of the active layer, diffusion layer, and protective layer.

[0033] When the active layer is elemental lithium metal, the introduction of the lithium metal layer into the composite negative electrode, on the one hand, improves the overall battery capacity due to the low potential of elemental lithium metal and its preferred quality. On the other hand, lithium ions can also deposit on the surface of the lithium metal layer through the liquid alloy layer, thereby helping to reduce the probability of lithium dendrites piercing the solid electrolyte and causing an internal short circuit in the battery.

[0034] In some embodiments of this application, the thickness of the diffusion layer is preferably 1 μm to 80 μm, and the diffusion layer loading is 0.1 to 10 mg / cm³. 2 This helps the diffusion layer to provide a more powerful volume expansion buffering effect and interfacial lithium diffusion capability.

[0035] In one embodiment of this application, the melting point of the liquid alloy layer is -40 to 35°C, and the alloying elements in the liquid alloy layer are selected from any two or more elements selected from the following elements: Na, K, Ga, Sn, In, Hg, Al, Mg, Zn, Bi, Pd, Cd, and Tl; and / or, the thickness of the liquid alloy layer is 10 nm to 30 μm, and the loading of the liquid alloy layer is less than 20 mg / cm³. 2 .

[0036] The liquid alloys with the above low melting points can be liquid at room temperature, and the types and amounts of the above liquid alloys also help to improve their lithium ion transport performance and conductivity. The preferred thickness of the liquid alloy layer helps to provide sufficient space for the growth of lithium dendrites.

[0037] In some embodiments of this application, the material form of the aforementioned negative electrode current collector is one-dimensional, two-dimensional, three-dimensional, or a combination thereof. Using the above types of negative electrode current collectors, especially three-dimensional current collectors, can result in more uniform lithium metal deposition and reduce the probability of lithium dendrite growth.

[0038] Furthermore, the structure of the preferred negative electrode current collector is selected from any one or more of the following: granular structure, fiber structure, layered structure, or three-dimensional network structure or three-dimensional foam cavity structure formed by interwoven layers.

[0039] Furthermore, the average particle size of the preferred granular structure is 0.5 mm to 50 mm, the thickness of the preferred layered structure is 1 μm to 100 μm, the cavity size in the preferred three-dimensional foam cavity structure is 5 nm to 100 μm, and the thickness of the three-dimensional skeleton in the preferred three-dimensional network structure and the preferred three-dimensional foam cavity structure is 2 μm to 1 mm.

[0040] Specifically, the negative electrode current collector is further preferably selected from copper balls, copper wires, zinc wires, aluminum wires, nickel wires, iron wires, titanium wires, iron-nickel alloy wires, copper foil, zinc foil, aluminum foil, nickel foil, iron foil, titanium foil, iron-nickel alloy foil, carbon film, carbon cloth, carbon paper, carbon fiber, graphene, MXene, conductive polymer non-metallic materials, foamed copper, foamed zinc, foamed nickel, foamed aluminum, foamed iron, foamed titanium, or foamed iron-nickel alloy, wherein the conductive polymer non-metallic material is selected from any one or more of polypyrrole compounds, polyphenylene sulfide compounds, polyaniline compounds, polythiophene compounds, poly(p-phenylene) compounds, and polyphthalocyanine compounds.

[0041] In another typical embodiment of this application, a method for preparing the above-mentioned composite negative electrode is provided. The method includes: step S1, loading an active layer onto a negative electrode current collector to obtain a bilayer structure material; step S2, loading a lithium-intercalating material and / or a material that can reversibly form an alloy or compound with lithium onto the active layer of the bilayer structure material to obtain a supported structure material; step S3, heating the supported structure material to pre-lithiate the lithium-intercalating material and / or the material that can reversibly form an alloy or compound with lithium into a diffusion layer, obtaining a diffusion layer-active layer-current collector three-layer structure material; and step S4, contacting and laminating the diffusion layer of the pre-lithiated material with the liquid alloy layer of the protective layer to obtain a composite negative electrode; wherein, the protective layer includes a liquid alloy layer and a polymer electrolyte layer stacked sequentially.

[0042] The above methods yielded the following results: Figure 1The composite anode with a stacked structure shown can be used as the anode in solid-state lithium batteries to address the issue of voltage plateau decline, reduce interfacial impedance, and suppress lithium dendrite growth, thereby improving the electrochemical performance of solid-state batteries. Simultaneously, it enhances and improves the overall electrical and safety performance of the battery. Furthermore, the above preparation method is simple to implement and has low production costs.

[0043] Furthermore, the active layer is preferably loaded onto the negative electrode current collector by rolling or stacking; the diffusion layer is preferably loaded onto the active layer of the bilayer material by coating, spraying or rolling. Further, the solvent used for coating or spraying slurry is preferably one or more of tetrahydrofuran, acetonitrile, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0044] In some embodiments of this application, the preferred heating temperature is 80–170°C, and the heating time is 2–10 hours.

[0045] In one embodiment of this application, the above preparation method further includes a protective layer preparation process, which includes: loading a slurry comprising a polymer, a lithium salt, and a solvent onto a substrate, drying it to obtain a polymer electrolyte layer; loading a liquid alloy onto the polymer electrolyte layer to obtain a protective layer; the mass ratio of polymer to lithium salt is 1:20 to 50:1, preferably 1:1 to 20:1; the polymer is a self-polymer or copolymer, and the monomers forming the polymer are selected from any one or more of amides, urethanes, ethers, carbonates, vinylidene fluoride, acrylonitrile, vinyl chloride, and ethylene oxide; and / or, the lithium salt is selected from any one or more of LiPF6, LiBF4, LiAsF6, LiDFOB, LiPO2F2, LiNO3, LiTFSI, or LFSI; and / or, the solvent is selected from any one or more of tetrahydrofuran, acetonitrile, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0046] In another typical embodiment of this application, a solid-state lithium battery is provided, including a negative electrode, which is the aforementioned composite negative electrode.

[0047] Solid-state lithium batteries, including the above composite negative electrodes, have high safety and excellent electrical performance.

[0048] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0049] Example 1

[0050] (1) Preparation of positive electrode sheet

[0051] First, 67g of LiNi 0.9 Co 0.05 Mn0.05 O2 cathode material, 28g Li6PS5Cl, 3g butadiene rubber binder, 1g acetylene black, and 1g carbon nanotubes were added to 100g toluene solvent and stirred under vacuum in a mixer for 6 hours to obtain a stable and uniform cathode slurry. The cathode slurry was then evenly coated on both sides of an aluminum foil, dried at 120 degrees Celsius, and rolled to obtain a cathode sheet.

[0052] (2) Preparation of solid electrolyte layer

[0053] Under a protective atmosphere, 95g of Li6PS5Cl and 5g of butadiene rubber binder were placed in 200g of toluene solution and stirred until a stable and uniform slurry was formed. The slurry was continuously coated onto the positive electrode obtained in step (1) and then dried at 80 degrees Celsius to obtain a positive electrode with a solid electrolyte layer, with the thickness of the solid electrolyte layer controlled to be 25μm.

[0054] (3) Preparation of protective layer

[0055] 4.40 g of PEO (molecular weight 1 million) and 2.87 g of LiTFSI were placed in 45 g of acetonitrile and stirred until a stable and homogeneous slurry was formed. This slurry was coated onto a polytetrafluoroethylene (PTFE) plate and dried at 80°C to obtain a polymer electrolyte layer. Then, Ga was applied by brush coating. 67 -In 20.5 -Sn 12.5 A negative electrode protective layer is obtained by coating a polymer electrolyte layer with a liquid alloy. The thickness of the liquid alloy layer is 5 μm, and the loading of the liquid alloy layer is 3 mg / cm³. 2 .

[0056] (4) Preparation of diffusion layer

[0057] 48g of graphite, 0.5g of acetylene black, 1g of polystyrene-butadiene rubber, and 0.5g of sodium carboxymethyl cellulose were placed in 75g of deionized water and stirred until a stable and homogeneous slurry was formed. This slurry was coated onto the lithium metal active layer of copper foil and then dried at 80°C to obtain a lithium-intercalating graphite coating with a thickness of 15μm and a graphite loading of 2mg / cm³. 2 In a dry chamber, the active layer (35μm lithium strip) is loaded onto the copper foil negative electrode current collector by rolling. The graphite-coated electrode sheet is stacked on the active layer, and the graphite coating is loaded onto the active layer by rolling. Then, the copper foil on the graphite coating is peeled off. The negative electrode is placed on a flat plate heater at 170 degrees Celsius and heated for 2 hours to pre-lithiate the graphite coating to obtain the negative electrode diffusion layer.

[0058] (5) Preparation of composite negative electrode sheet

[0059] In a dry chamber, the protective layer is peeled off from the polytetrafluoroethylene plate and attached to the pre-lithiated diffusion layer. The alloy layer in the protective layer faces the direction of the diffusion layer, resulting in a composite negative electrode material with a structure from top to bottom of protective layer-diffusion layer-active layer-current collector.

[0060] (6) Preparation of solid-state lithium batteries

[0061] In a dry chamber, the composite negative electrode obtained in step (5) is die-cut and aligned with the positive electrode sheet with a solid electrolyte layer obtained in step (2). Positive and negative electrode tabs are welded on respectively, and the solid lithium battery of this embodiment is obtained by vacuum sealing with aluminum-plastic film. The solid lithium battery is then subjected to 0.1C charge-discharge cycle at room temperature.

[0062] Example 2

[0063] The difference from Example 1 is that the graphite material in step (4) is replaced with porous carbon material. The porous carbon material has a pore size of 60 nm and a porosity of 40%, and finally a solid-state lithium battery is obtained.

[0064] Example 3

[0065] The difference from Example 2 is that the pore size of the porous carbon material in step (4) is 2 μm and the porosity is 45%, which finally yields a solid-state lithium battery.

[0066] Example 4

[0067] The difference from Example 2 is that the pore size of the porous carbon material in step (4) is 5 μm and the porosity is 40%, which finally yields a solid-state lithium battery.

[0068] Example 5

[0069] The difference from Example 2 is that the pore size of the porous carbon material in step (4) is 100 nm and the porosity is 60%, and a solid-state lithium battery is finally obtained.

[0070] Example 6

[0071] The difference from Example 2 is that the pore size of the porous carbon material in step (4) is 1 nm and the porosity is 85%, and a solid-state lithium battery is finally obtained.

[0072] Example 7

[0073] The difference from Example 2 is that the pore size of the porous carbon material in step (4) is 40 μm and the porosity is 20%, and a solid-state lithium battery is finally obtained.

[0074] Example 8

[0075] The difference from Example 1 is that the thickness of the diffusion layer in step (4) is 30 μm and the diffusion layer loading is 4 mg / cm³. 2 Ultimately, this leads to solid-state lithium batteries.

[0076] Example 9

[0077] The difference from Example 1 is that the thickness of the liquid alloy layer in step (3) is 10 μm, and the loading of the liquid alloy layer is 6 mg / cm³. 2 Ultimately, this leads to solid-state lithium batteries.

[0078] Example 10

[0079] The difference from Example 1 is that the liquid alloy layer in step (3) is Ga. 75.5 -In 24.5 Ultimately, this leads to solid-state lithium batteries.

[0080] Example 11

[0081] The difference from Example 1 is that the mass of the lithium metal element loaded on the copper foil in step (4) is changed so that the mass of the lithium metal element is 10wt% of the total mass of the active layer, diffusion layer and protective layer, and a solid-state lithium battery is finally obtained.

[0082] Example 12

[0083] The difference from Example 1 is that the mass of the lithium metal element loaded on the copper foil in step (4) is changed so that the mass of the lithium metal element is 30wt% of the total mass of the active layer, diffusion layer and protective layer, and a solid-state lithium battery is finally obtained.

[0084] Example 13

[0085] The difference from Example 1 is that the mass of the lithium metal element loaded on the copper foil in step (4) is changed so that the mass of the lithium metal element is 3wt% of the total mass of the active layer, diffusion layer and protective layer, and a solid-state lithium battery is finally obtained.

[0086] Example 14

[0087] The difference from Example 1 is that the negative electrode current collector in step (4) is a three-dimensional copper cloth with a thickness of 20 μm, and a solid-state lithium battery is finally obtained.

[0088] Example 15

[0089] The difference from Example 1 is that the graphite material in step (4) is replaced with silicon-carbon material, wherein the silicon content in the silicon-carbon material is 10%, and a solid-state lithium battery is finally obtained.

[0090] Example 16

[0091] The difference from Example 1 is that the graphite material in step (4) is replaced with lithium titanate material, and a solid-state lithium battery is finally obtained.

[0092] Example 17

[0093] The difference from Example 1 is that the graphite material in step (4) is replaced with silver-carbon material, wherein the silver content in the silver-carbon material is 25%, the particle size of the silver particles is 30nm, and the particle size of the carbon particles is 35nm, and finally a solid-state lithium battery is obtained.

[0094] Example 18

[0095] The difference from Example 1 is that the heating and pre-lithiation temperature in step (4) is 80°C, and a solid-state lithium battery is finally obtained.

[0096] Example 19

[0097] The difference from Example 1 is that the heating temperature for pre-lithiation in step (4) is 120°C, and a solid-state lithium battery is finally obtained.

[0098] Example 20

[0099] The difference from Example 1 is that the heating temperature for pre-lithiation in step (4) is 70°C, and a solid-state lithium battery is finally obtained.

[0100] Example 21

[0101] The difference from Example 1 is that in step (2), the mass ratio of butadiene rubber to Li6PS5Cl is 8:2, and a solid-state lithium battery is finally obtained.

[0102] Example 22

[0103] The difference from Example 1 is that in step (4), the negative electrode is heated on a flat plate heater at 170 degrees Celsius for 5 hours to pre-lithiate the graphite coating and obtain the negative electrode diffusion layer.

[0104] Example 23

[0105] The difference from Example 1 is that in step (4), the negative electrode is heated on a flat plate heater at 170 degrees Celsius for 10 hours to pre-lithiate the graphite coating and obtain the negative electrode diffusion layer.

[0106] Example 24

[0107] The difference from Example 1 is that in step (4), the negative electrode is heated on a flat plate heater at 170 degrees Celsius for 12 hours to pre-lithiate the graphite coating and obtain the negative electrode diffusion layer.

[0108] Example 25

[0109] The difference from Example 1 is that in step (4), the negative electrode is heated on a flat plate heater at 170 degrees Celsius for 1.5 hours to pre-lithiate the graphite coating and obtain the negative electrode diffusion layer.

[0110] Comparative Example 1

[0111] The difference from Example 1 is that the negative electrode material has no diffusion layer and protective layer, that is, the negative electrode material is pure lithium metal.

[0112] Comparative Example 2

[0113] The difference from Example 1 is that the negative electrode material has no diffusion layer, that is, the structure of the negative electrode material from top to bottom is protective layer-active layer-current collector.

[0114] Comparative Example 3

[0115] The difference from Example 1 is that the negative electrode material has no active layer and diffusion layer, that is, the structure of the negative electrode material from top to bottom is a protective layer-current collector.

[0116] Table 1 lists the data for the first-cycle discharge specific capacity, average median discharge voltage, and cycle life of Examples 1 to 25 and Comparative Examples 1 to 3 above.

[0117] Table 1

[0118]

[0119]

[0120] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0121] Compared to existing technologies, the composite anode of this invention incorporates a diffusion layer between the liquid alloy layer and the active lithium metal layer. Pre-lithiation of the diffusion layer enhances its electronegativity and lithiophilicity, while simultaneously allowing lithium atoms to escape more rapidly. This diffusion layer facilitates a transition in the delithiation mechanism, thereby increasing the lithium atom diffusion coefficient in the alloy layer. This improves lithium diffusion kinetics in the liquid alloy layer, enhances interfacial lithium diffusion capacity, and addresses the issue of battery voltage plateau decline. Furthermore, constructing a protective layer on the diffusion layer surface improves solid-solid compatibility between the composite anode and the solid electrolyte material, reduces interfacial impedance, and inhibits lithium dendrite growth, thus enhancing the electrochemical performance of the solid-state battery. Meanwhile, the composite negative electrode provided by this invention contains a liquid alloy layer, which is liquid at room temperature. Compared with the solid state, the liquid state has less steric hindrance. Therefore, when this composite negative electrode is used as a lithium battery negative electrode, the lithium dendrites growing on the negative electrode will preferentially grow in the liquid alloy rather than towards the solid electrolyte (polymer electrolyte layer). This can effectively reduce the probability of internal short circuits caused by lithium dendrite growth, thereby greatly improving the battery's safety performance. Moreover, the liquid alloy layer also has excellent lithium-ion transport performance. Furthermore, the liquid alloy layer in the negative electrode provided by this invention is placed close to the solid electrolyte. Compared with the contact between the solid material and the solid electrolyte in the negative electrode, the contact between the liquid alloy layer and the solid electrolyte layer is better, which is more conducive to lithium-ion transport. In addition, the liquid alloy layer also has excellent electronic conductivity, which also helps electron transport, enabling the negative electrode to carry out electrochemical reactions quickly, reducing the negative electrode impedance, and thus helping to improve the overall performance of the battery.

[0122] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A composite negative electrode, characterized in that, The composite negative electrode includes a protective layer, a diffusion layer, an active layer, and a negative electrode current collector stacked sequentially. The diffusion layer includes a pre-lithiated lithium-intercalable material and / or a pre-lithiated material that can reversibly form an alloy or compound with lithium. The protective layer includes a liquid alloy layer and a polymer electrolyte layer stacked sequentially. The liquid alloy layer is in contact with the diffusion layer. The active layer is composed of elemental lithium metal, and the mass of the elemental lithium metal is 5-90 wt% of the total mass of the active layer, the diffusion layer, and the protective layer. The thickness of the diffusion layer is 1 μm to 80 μm, and the loading of the diffusion layer is 0.1 to 10 mg / cm³. 2 ; The lithium-intercalable material is selected from any one or more of porous carbon materials, graphite, lithium titanate, transition metals, bismuth fluoride oxides, and bismuth fluoride oxides; the material that can reversibly form an alloy with lithium is selected from any one or more of elemental silicon, elemental silver, elemental germanium, elemental gold, elemental platinum, and elemental tin; and the material that can reversibly form a compound with lithium is selected from any one or more of transition metal oxides and silicon oxides.

2. The composite negative electrode according to claim 1, characterized in that, The pore size of the porous carbon material is 1 nm to 40 μm; the porosity of the porous carbon material is 20% to 85%.

3. The composite negative electrode according to claim 2, characterized in that, The pore size of the porous carbon material is 0.1~5μm.

4. The composite negative electrode according to claim 2, characterized in that, The porosity of the porous carbon material is 40-60%.

5. The composite negative electrode according to any one of claims 1 to 4, characterized in that, The liquid alloy layer has an alloy melting point of -40 to 35°C, and the alloying elements in the liquid alloy layer are selected from any two or more elements chosen from the following elements: Na, K, Ga, Sn, In, Hg, Al, Mg, Zn, Bi, Pd, Cd, and Tl; and / or, The thickness of the liquid alloy layer is 10 nm to 30 μm, and the loading of the liquid alloy layer is less than 20 mg / cm³. 2 .

6. The composite negative electrode according to any one of claims 1 to 4, characterized in that, The negative electrode current collector has a material form of one-dimensional, two-dimensional, three-dimensional, or a combination thereof.

7. The composite negative electrode according to claim 6, characterized in that, The structure of the negative electrode current collector is selected from any one or more of the following: granular structure, fiber structure, layered structure, three-dimensional network structure formed by interwoven layers, or three-dimensional foam cavity structure.

8. The composite negative electrode according to claim 7, characterized in that, The average particle size of the granular structure is 0.5 mm to 50 mm.

9. The composite negative electrode according to claim 7, characterized in that, The thickness of the layered structure is 1 μm to 100 μm.

10. The composite negative electrode according to claim 7, characterized in that, The cavity size in the three-dimensional foam cavity structure is 5nm~100μm.

11. The composite negative electrode according to claim 7, characterized in that, The thickness of the three-dimensional skeleton in the three-dimensional network structure and the three-dimensional foam cavity structure is 2μm~1mm.

12. The composite negative electrode according to claim 6, characterized in that, The negative electrode current collector is selected from copper balls, copper wire, zinc wire, aluminum wire, nickel wire, iron wire, titanium wire, iron-nickel alloy wire, copper foil, zinc foil, aluminum foil, nickel foil, iron foil, titanium foil, iron-nickel alloy foil, carbon film, carbon cloth, carbon paper, carbon fiber, graphene, MXene, conductive polymer non-metallic materials, foamed copper, foamed zinc, foamed nickel, foamed aluminum, foamed iron, foamed titanium, or foamed iron-nickel alloy, wherein the conductive polymer non-metallic material is selected from any one or more of polypyrrole compounds, polyphenylene sulfide compounds, polyaniline compounds, polythiophene compounds, poly(p-phenylene) compounds, and polyphthalocyanine compounds.

13. A method for preparing the composite negative electrode according to any one of claims 1 to 12, characterized in that, The preparation method includes: Step S1: Load the active layer onto the negative electrode current collector to obtain a bilayer structure material; Step S2: Load a lithium-intercalable material and / or a material that can reversibly form an alloy or compound with lithium onto the active layer of the bilayer structure material to obtain a supported structure material; Step S3: The supported structural material is heated, and the lithium-intercalable material and / or the material that can reversibly form an alloy or compound with lithium is pre-lithiated to form a diffusion layer, resulting in a three-layer structure material of diffusion layer-active layer-current collector; and Step S4: The diffusion layer and the liquid alloy layer of the protective layer are brought into contact and laminated to obtain the composite negative electrode; The protective layer comprises the liquid alloy layer and the polymer electrolyte layer stacked sequentially.

14. The preparation method according to claim 13, characterized in that, The heating temperature is 80~170℃, and the heating time is 2 h~10 h.

15. The preparation method according to claim 13 or 14, characterized in that, The preparation method further includes a process for preparing the protective layer, the preparation process comprising: A slurry comprising a polymer, a lithium salt, and a solvent is loaded onto a substrate and dried to obtain the polymer electrolyte layer. The protective layer is obtained by loading liquid alloy liquid onto the polymer electrolyte layer; The mass ratio of the polymer to the lithium salt is 1:20 to 50:1; the polymer is a self-polymer or copolymer, and the monomers forming the polymer are selected from any one or more of amides, urethanes, ethers, carbonates, vinylidene fluoride, acrylonitrile, vinyl chloride, and ethylene oxide; and / or, The lithium salt is selected from any one or more of LiPF6, LiBF4, LiAsF6, LiDFOB, LiPO2F2, LiNO3, LiTFSI, or LFSI.

16. The preparation method according to claim 15, characterized in that, The mass ratio of the polymer to the lithium salt is 1:1 to 20:

1.

17. A solid-state lithium battery, comprising a negative electrode, characterized in that, The negative electrode is a composite negative electrode according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Solid-state electrolyte with negative electrode interface layer, preparation method and solid-state battery

    CN110518278A

  • Aluminum negative electrode material, preparation method and secondary battery

    CN111326717A

  • Composite negative electrode, solid-state lithium battery and preparation method of solid-state lithium battery

    CN112420978A